Análise por CG-EM do óleo essencial de Eucalyptus camaldulensis Dehn. influenciado por doses de NPK - Santos, Ricardo Carvalho dos (2011)
This study aimed at analyzing by GC-MS of the essential oil of Eucalyptus camaldulensis Denh. influenced by doses of NPK. The research is justified by the need to observe the influence of NPK fertilization on the concentration of chemical constituents of essential oil of Eucalyptus camaldulensis Denh., there is no information on the subject for the species under study. Samples were collected in the first hours of the morning, about 07:30 a.m. in the experimental field of Embrapa Roraima. Was extracted from the essential oil samples by hydrodistillation process with Clevenger-type system for 4 hours at the Laboratory of Natural Products, Universidade Federal de Roraima. The volatile oils obtained were packaged in amber glass bottles and kept refrigerated for later chemical analysis. With the help of Shimadzu gas chromatograph coupled to a detector quadrupole mass spectrometry, QP-5050th, chromatographic analysis was performed, which provided qualitative and quantitative information. These quantitative data were applied to statistical models in order to obtain information on the influence of NPK fertilization on the concentration of chemical constituents of essential oil. This may confirm the influence of NPK fertilization, increasing or decreasing concentrations of the chemical composition of the monoterpene hydrocarbon groups, oxygenated monoterpenes, sesquiterpene hydrocarbons and oxygenated sesquiterpenes as well as the constituents β-pinene and eucalyptol, except the p-cymene, the which was not influenced by the levels of NPK. Since the chemical constituents carvacrol, and espatulenol globulol not been possible to analyze the influence of NPK fertilization for these chemicals.